A simple and fast guideline for generating enhanced/squared envelope spectra from spectral coherence for bearing fault diagnosis. (1st May 2019) - Wang, Dong; Zhao, Xuejun; Kou, Lin-Lin; Qin, Yong; Zhao, Yang; Tsui, Kwok-Leung
Graphical abstract: The flowchart of the proposed guideline for generating EES from spectral coherence for bearing fault diagnosis: (a) a raw inner race fault signal; (b) frequency spectrum of (a); (c) spectral coherence; (d) the proposed guideline; (e) EES generated from spectral coherence in a spectral frequency band from 1153 Hz to 1581 Hz; (f) EES generated from spectral coherence in a spectral frequency band from 1991 Hz to 2419 Hz; (g) EES generated from spectral coherence in a spectral frequency band from 2874 Hz to 3302 Hz; (h) EES generated from spectral coherence in a spectral frequency band from 4549 Hz to 4977 Hz. Highlights: Spectral coherence lacks of a guideline for its integration over spectral frequency bands. The L 2/ L 1 ratio is commonly used to characterize the impulsiveness and cyclostationarity of bearing fault signals. A simple and fast guideline for integrating spectral coherence was proposed. Generating enhanced/squared envelope spectrum from spectral coherence was realized. Spectral coherence integrated with the guideline for bearing fault diagnosis was proposed. Abstract: Rolling element bearings are widely used in machines to support rotating shafts and their health conditions degrade over time due to harsh working conditions. Once a fault occurs on the surface of either an inner race or an outer race, impacts caused by rollers striking the fault surface excite resonant frequencies of a machine and then repetitive transients are observed in vibration signals collected from the casing of the machine. Spectral correlation and its normalized version, spectral coherence, are a function of spectral frequency and cyclic frequency, and they are able to simultaneously display resonant frequency bands and bearing fault frequencies. Moreover, it has been proved that integrating spectral correlation over an informative spectral frequency band is related to a squared envelope spectrum which is more conveniently used to detect bearing fault frequencies than the direct inspection of the bi-spectra map of spectral correlation/spectral coherence. Therefore, generating enhanced/squared envelope spectra from spectral correlation/spectral coherence is an important step for the use of spectral correlation/spectral coherence for bearing fault diagnosis. However, in the past years, determining informative spectral frequency bands for generating enhanced/squared envelope spectra from spectral correlation/spectral coherence mainly depends on expertise and careful observations from spectral correlation/spectral coherence. In the case of weak bearing fault frequencies and strong interruptions from other cyclic frequencies, it is not easy for users to determine an informative spectral frequency band for generating an enhanced/squared envelope spectrum from spectral correlation/spectral coherence for bearing fault diagnosis. To solve this problem, a simple and fast guideline is proposed in this paper. Laboratorial bearing fault data and industrial railway axle bearing fault data are used to illustrate how the proposed guideline works. Results showed that the proposed guideline is effective in determining informative spectral frequency bands for generating enhanced/squared envelope spectra from spectral coherence for bearing fault diagnosis. Comparisons with the fast Kurtogram and an enhanced squared envelope spectrum generated from integrating spectral coherence over the whole spectral frequency band are conducted to highlight the superiority of the proposed guideline.